STUDI PRODUKSI DAN KUALITAS RUMPUT GAJAH (Pennisetum purpureum) VARIETAS THAILAND YANG DIPUPUK DENGAN KOMBINASI ORGANIK-UREA - Hidayat, Nur; Suwarno, - (Pastura, 2014)
Thailand-variety elephant grass fertilized with organic and urea combination was conducted from August 1st up to Novembre 30th, 2009. The purpose of this study was to know the best interaction of organic-urea levels on the production and quality aspects of Thailand-variety elephant grass. The method used was experimental, 3x4 factorial pattern, using completely randomized design (CRD). There were 3 replicates in each treatment combination. The first factor was organic fertilizer (3 levels: k0= 0 ton/ha, k1= 20 tons/ha, and k2 = 40 tons/ ha), and the second factor was urea (4 levels: R0 = 0 kg/ha, R1 = 150 kg/ha, R2 = 300 kg/ha, and R3 = 450 kg/ ha). Variables measured were the number of tillers, plant height, the number of leaves/bunch, fresh weight, dry weight, agronomic efficiency, and crude protein and crude fiber concentrations. The result of analisys of variance showed that organic fertilizer had significant effect (P < 0.05) on the tiller/bunch, number of leaves/bunch, dry matter yield, and crude protein, but gave highly significant effect (P < 0.01) on fresh yield, and no significant effect (P > 0.05) on the height of plant and crude fiber concentration. Whereas urea gave a significant effect (P < 0.05) on the number tiller/bunch, and highly significant effect (P < 0.01) on fresh and dry matter yield and crude protein concentration, but no significant effect (P > 0.05) on height of plant, the number of leaves to stems ratio, and crude fiber concentration. The conclusions of this study for the management of Thailand-variety elephant grass, the best organic-urea fertilizer combination was at the level of 40 tons of organic fertilizer/ha/ defoliation and 300 kg of urea/ha/defoliation, showed from the agronomy aspects such as the number of tillers/ bunch, the height of plant, the number of leaves/bunch, fresh and dry matter yields, and quality aspect include crude protein and crude fiber concentration.
Keywords: compost, urea, agronomic, crude protein and fiber concentration